Experience as One of the Factors Strengthening the Criticism of People’s Outlook - Mačianskas, Feliksas (Problemos, 1968)
With reference to some specimen of Lithuanian folk art the paper attempts to show the period, when people conceived the surrounding world as existing according to the same principles as the world of human beings. Man of that time was not aware of the essential difference between animate and inanimate nature. Further experience, however, gained as a result of labour helped man to better orientate himself in his surroundings, to discover some aspects of things and objects, laws of nature, to realize many of their interrelations, etc. Despite the fact, that there are still many things incomprehensible, mysterious, frightening and subordinating, which sometimes make a man act against his will, his outlook is becoming more critical. As his knowledge grows, man begins to fight for his existence more consciously, subjecting nature to his interests. All these factors are reflected in folk art.